2015
DOI: 10.1021/acs.jnatprod.5b00766
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Antiepileptic Activity of C21 Steroidal Glycosides from the Roots of Cynanchum wilfordii

Abstract: Nine new C21 steroidal glycosides, named cynawilfosides A-I (1-9), along with 12 known compounds were isolated from the roots of Cynanchum wilfordii. The structures of the new compounds were elucidated by spectroscopic analysis and chemical methods. The five major components, cynawilfoside A (1), cynauricoside A (11), wilfoside C1N (16), wilfoside K1N (17), and cyanoauriculoside G (18), exhibited significant protection activity in a maximal electroshock (MES)-induced mouse seizure model with ED50 values of 48.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…5), which suggested that metabolismdependent ROS production may be the major reason for the rise in FSC and shape alteration. MTE, in our experiments, was a crude extract containing abundant C 21 steroids with anti-cancer activity, which have been previously extracted from several kinds of herbal medicine and have presented cytotoxicity in various cancer cell lines (Li et al, 2016;Yin et al, 2016). From M. tenacissimae, more than 40 kinds of C-21 steroidal glycosides have been isolated (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…5), which suggested that metabolismdependent ROS production may be the major reason for the rise in FSC and shape alteration. MTE, in our experiments, was a crude extract containing abundant C 21 steroids with anti-cancer activity, which have been previously extracted from several kinds of herbal medicine and have presented cytotoxicity in various cancer cell lines (Li et al, 2016;Yin et al, 2016). From M. tenacissimae, more than 40 kinds of C-21 steroidal glycosides have been isolated (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that CAR was incorrectly used in eight of the 13 products distributed as CWR, including possible confusion of CWR and CAR [ 5 ]. Previous phytochemical investigations of CWR identified the presence of pregnane glycosides, acetophenones, and humulanolides [ 6 , 7 , 8 , 9 , 10 , 11 ]. Although there are several reports on ingredient research using materials of CWA and CAR available on the market, they may not be of the precise species.…”
Section: Introductionmentioning
confidence: 99%
“…Bunge Auriculate Root (Baishouwu) is an appellative name for the root tubers of Cynanchum auriculatum, Cynanchum bungei , and Cynanchum wilfordii in China, which is a famous tonic drug in TCM and known for its functions in enriching vital essence and enhancing immunity (Shan et al, 2006 ). Pharmacological studies suggested that Bunge Auriculate Root exhibits antitumor, antidepressant, anti-inflammatory, and antiepileptic activities (Peng et al, 2008 ; Yang et al, 2011 , 2014 ; Li et al, 2016 ). In addition, the root of Cynanchum otophyllum (Qingyangshen) has antifungal and antiepileptic activities (Zhao et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%